The general form of an exponential function is the following
![\begin{gathered} y=ab^x \\ a\\e0 \\ b>1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9shc79j04mj4hi1opcs9dzty2q88bqxmqk.png)
we can find the values for a and b using the known values for x and y. First, notice that when x = 0, y =51, then, if we put these values on the general form, we get:
![\begin{gathered} 51=ab⁰=a(1)=a \\ \Rightarrow a=51 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/irgfepevn7bf04c7id8hhc40mk6duga6w5.png)
next, we have that when x = -1, y = 17. We also know now that a = 51, then, using this information, we can find the value of b:
![\begin{gathered} 17=51b^(-1) \\ \Rightarrow17=(51)/(b) \\ \Rightarrow17b=51 \\ \Rightarrow b=(51)/(17)=3 \\ b=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9a8d8fkty4fgrv1agbnj0gqyz3i3jfe5fm.png)
therefore, the exponential function is y = 51(3)^x